2006
DOI: 10.1002/ijc.21913
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking, alcohol drinking and non‐Hodgkin's lymphoma: A European multicenter case‐control study (Epilymph)

Abstract: To study the role of tobacco smoking and alcohol drinking in the etiology of non-Hodgkin's lymphoma (NHL), we conducted a multicenter case-control study in Spain, France, Germany, Italy, Ireland and Czech Republic between 1998 and 2004, which included 1,742 cases of NHL and 2,465 controls matched on age, sex and recruitment area. Tobacco smoking was not associated with the risk of NHL overall or with risk of specific histological subtypes. Similarly, there was no association between alcohol drinking and the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 51 publications
3
33
1
Order By: Relevance
“…Although several studies have reported no association between smoking and the risk of lymphoma (3,10,11), the pooled analysis of the International Lymphoma Epidemiology Consortium study revealed a positive association between smoking and the risk of non-Hodgkin's lymphoma [OR (95% CI), reference for never smokers and 1.07 (1.00-1.15) for ever smokers], suggesting that smoking has carcinogenic effects (9). Consistent with this, our present study also showed a positive association between smoking exposure and lymphoma [OR (95% CI), reference for never smokers and 1.24 (1.02-1.51) for ever smokers] along with heterogeneity of this risk between each of the major histologic subtypes: follicular lymphoma, Hodgkin's lymphoma, marginal zone lymphoma, and diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although several studies have reported no association between smoking and the risk of lymphoma (3,10,11), the pooled analysis of the International Lymphoma Epidemiology Consortium study revealed a positive association between smoking and the risk of non-Hodgkin's lymphoma [OR (95% CI), reference for never smokers and 1.07 (1.00-1.15) for ever smokers], suggesting that smoking has carcinogenic effects (9). Consistent with this, our present study also showed a positive association between smoking exposure and lymphoma [OR (95% CI), reference for never smokers and 1.24 (1.02-1.51) for ever smokers] along with heterogeneity of this risk between each of the major histologic subtypes: follicular lymphoma, Hodgkin's lymphoma, marginal zone lymphoma, and diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 98%
“…Several case-control and cohort studies have investigated the association of alcohol intake and smoking with the risk of Hodgkin's and non-Hodgkin's lymphoma in nonAsian populations, with most suggesting an inverse association for alcohol consumption with the risk of malignant lymphoma (1-6) versus inconsistent results for smoking (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, little research has been conducted in Asian populations, particularly with regard to the effects of smoking and alcohol consumption on the risk of malignant lymphoma subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Details about the study have been described elsewhere. 16 Briefly, cases were all consecutive adult patients first diagnosed with lymphoma during the study period, resident in the referral area of the participating center. The diagnosis was classified according to the 2001 World Health Organization classification of lymphoma, 17 and slides of about 20% of cases from each center were reviewed centrally by a panel of pathologists, coordinated by MM.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies reported an inverse association between alcohol consumption and the risk of ML (1)(2)(3)(4)(5)(6), but reported inconsistent results with regard to that of PCM (6)(7)(8)(9). In contrast to the number of studies in Western populations, however, little research has been conducted in Asian populations.…”
Section: Introductionmentioning
confidence: 99%